Characterization of historical coating mortars of La Ceramo factory in Valencia - Sutti, Marcela Luana [UNESP]; Silva de Aguiar, Maiara Oliveira [UNESP]; Fioriti, Cesar Fabiano [UNESP]; Hengling Christofani, Maria Paula [UNESP] (Univ Politecnica Valencia, Editorial Upv, 2019)
The objective of this paper was to characterize historical coating mortars taken from the La Ceramo factory, in Valencia, by means of historical, in situ and sample collection at various points in the building, for subsequent laboratory tests. The physical-mechanical characteristics studied were: compressive strength, water content, granulometry by sieving method, identification of calcium carbonate with hydrochloric acid, surface hardness, water absorption, apparent porosity and bulk density. The results showed that the mortars composed of cement and lime collected did not present very positive characteristics in the aspects analyzed in this study, resulting in material with low quality, both in its initial composition and in function of the external influences suffered over time. Regarding the other areas of lime mortar, these presented better results, although less resistant than those of cement, were shown to have good quality. It can also be observed that lime mortars, even having a similar composition in their origin, when applied at different points of the factory acquired uneven characteristics over time, directly related to the local conditions of the coated walls. Finally, the need for preventive conservation in buildings of historical interest makes this paper of investigative and scientific nature, since the knowledge of the original materials is the initial step to a good intervention and not to accelerate the process of degradation of historical constructions.
Keywords: characterization; coating mortars; degradation; historical building